Nidal Embolization of Brain Arteriovenous Malformations Using Onyx in 94 Patients - Mounayer, C.; Hammami, N.; Piotin, M.; Spelle, L.; Benndorf, G.; Kessler, I.; Moret, J. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: To report our experience in the treatment of brain arteriovenous malformations (BAVMs) using Onyx (ev3, Irvine, Calif).Patients and METHODS: From January 1999 to October 2004, 94 patients with BAVMs were treated endovascularly in our department. They were 51 (54%) men and 43 (46%) women with a mean age of 32 years. A total of 210 endovascular procedures were performed with Onyx as the sole embolic agent in 88 procedures; Onyx and n-butyl cyanoacrylate (n-BCA) were used in combination in 50 procedures, and n-BCA alone was used in 72 procedures.RESULTS: The course of endovascular treatment was completed in 53 patients. In 26 patients (49%, 26/53) an angiographic cure was achieved using embolization as the sole therapeutic technique. Seven (13%, 7/53) patients underwent a surgical resection of the residual BAVM nidus, 20 (38%, 20/53) patients underwent radiosurgical treatment after nidal size reduction <2 cm was accomplished by endovascular treatment. Further endovascular treatment was planned in 33 patients, whereas in 5 patients, the continuation of embolization was aborted due to difficult nidus catheterization. Procedure-related permanent neurologic deficits were observed in 8 (8.5%, 8/94) patients. There were 3 procedure-related deaths.CONCLUSION: Onyx is suitable for brain BAVM embolizations and allows obtaining higher rates of anatomic cures compared with those obtained previously with other embolic agents.